One Digital Platform to Seek Quality Education for Everyone - K. V. Y. S. Kumara; R. B. Ranasinghe; B. D. H. Madhuranga; D. G. T. S. Gunasekara; D. I. De Silva; P. Samarasekara (International Journal of Engineering and Management Research, 2022)
The primary goal of this digital educational platform is to deliver high-quality educational possibilities to people looking for a degree or similar graded programs, tuition classes, and postgraduate programs provided by universities internationally and nationally. Furthermore, by advertising on our web platform, educational institutions will be able to improve the popularity of their courses and services. There will also be the opportunity to donate financial contributions to campaigns or organizations that will help persons in need of educational assistance. In addition, our development team proposed an idea about a component called volunteer support, which allows users to join up as volunteers for specific organizational initiatives that promote educational campaigns. There will also be several account types for system administrators, users searching for services, and organizations promoting educational programs and volunteer opportunities. The account's capabilities differ depending on the type of user account. The primary objectives of this thesis are to provide the concept of a system that simplifies the process of locating and advertising educational needs, opportunities, and services while providing a way to help people in need of a helping hand.